Tower of London - Hibbert, Christopher, 1924-2008.; Newsweek, inc. Book Division (New York : Newsweek, 1971)
Contains section, " The Tower of London in literature." [page 137- 160].
A castle for the conqueror -- Times of trouble -- The Tudor prison -- The shadow of the axe -- In dungeons dire -- Menagerie, mint and museum -- The tower endures.
Bibliography: p. 169.
Keywords: Tower of London (London, England); London (England) -- Buildings, structures, etc; Fortification -- England -- London -- History; Prisons -- England -- London -- History; London (England) -- History; London -- Tower of London